Making future taxonomy of Niphargus (Crustacea: Amphipoda: Niphargidae) in the Middle East easier: DELTA database of Middle East species with description of four new species from Iran - Esmaeili-Rineh, Somayeh; Sari, Alireza; Fišer, Cene (Zootaxa, 2015)
Four new species from the amphipod genus Niphargus are described, namely N. borisi sp. nov., N. bisitunicus sp. nov., N. darvishi sp. nov. and N. sharifi sp. nov. All four species of this predominantly subterranean genus were collected from springs in the Western region of Iran (Zagros region), which is the eastern borderline of the genus range. The species are morphologically diagnosed, described and illustrated. With these newly described species, the total number of Niphargus species in the Middle East reaches twenty-three. In order to facilitate the identification of Niphargus species in the region and to make future taxonomy of the genus easier, we have compiled a database in DEscription Language for TAxonomy (DELTA) using 23 diagnostic traits for these 23 species and subspecies identified in the Middle East. The database is available on the web as supplementary material whereas the dichotomous identification key automatically generated from the database for routine use is provided as a part of the paper.